2021
DOI: 10.2320/matertrans.mt-l2021011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Area Ratio on the Galvanic Corrosion of AZX611 Magnesium Alloy/A6N01 Aluminum Alloy Joint

Abstract: Galvanic corrosion at the joint of AZX611 magnesium (anode) and A6N01 aluminum (cathode) in 1 mass% NaCl solution with different cathode/anode area ratios was evaluated. The galvanic potential was different depending on the area ratio. The anode galvanic current density increased with increasing the area ratio. Anode and cathode weight loss corrosion rates, and the average of anode current densities, were linearly related to the logarithm of the area ratio with different slopes. Scanning vibration electrode te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…In detail, the titanium alloy maintains a consistent cathodic surface area, while the anodic area of carbon steel varies. This variation leads to a fluctuating anodic-to-cathodic area ratio, which is a crucial factor in galvanic corrosion [45][46][47][48]. The electrochemical principle that governs this behavior is based on the fact that the corrosion rate through the galvanic couple is a function of the surface area of both the anode and cathode.…”
Section: Impact Of Thickness Ratio On Corrosion Ratementioning
confidence: 99%
“…In detail, the titanium alloy maintains a consistent cathodic surface area, while the anodic area of carbon steel varies. This variation leads to a fluctuating anodic-to-cathodic area ratio, which is a crucial factor in galvanic corrosion [45][46][47][48]. The electrochemical principle that governs this behavior is based on the fact that the corrosion rate through the galvanic couple is a function of the surface area of both the anode and cathode.…”
Section: Impact Of Thickness Ratio On Corrosion Ratementioning
confidence: 99%
“…It was found that Mg-RE-TM alloy systems containing rare earth elements and transition metal elements with appropriate ratios exhibit excellent mechanical properties. This is mainly attributed to the formation of second phases with a long-period stacked ordered (LPSO) structure in the magnesium alloys [28][29][30]. At present, several LPSO structures have been found, including 10H, 12H, 14H, 15R, 18R, 21R, and 24R LPSO phases, of which 18R and 14H are the most common types [31].…”
Section: Galvanic Corrosionmentioning
confidence: 99%
“…Because it uses calculus to transform macroscopic electrochemical parameters into the organic coupling of electrochemical parameters in small areas, it can reflect the differences of electrochemical properties in different areas on the surface of aluminum alloy coupling and can effectively extract the corrosion characteristics and preferred corrosion areas of aluminum alloy galvanic corrosion through analysis. It is of great significance to explore the mechanism and process of complex galvanic corrosion of aluminum alloy [58]. Shi et al [49] used array electrode technology to explore the galvanic corrosion behavior of trimetals and found that the dielectric environment in 3.5 wt.% NaCl solution had a high conductivity, and the spatial arrangement of electrodes had little impact on the galvanic corrosion of trimetals.…”
Section: Wire Beam Electrodes (Wbe) Technologymentioning
confidence: 99%